A LTI/LQE scheme for real time rotor component load estimation - Prasad, J.V.R.; Mballo, C.E. (My University, 2017)
Accurate and real-time load monitoring of vital components located in the rotor system is important not only for inferring usage and estimating fatigue in those components but also for developing load alleviation control schemes. An approach for on-line estimation of rotor component loads is presented in this paper in which a linear time invariant (LTI) model of helicopter coupled body/rotor dynamics is combined with a Linear Quadratic Estimator (LQE), which is designed to correct LTI model state response using fixed system measurements. The developed LTI/LQE scheme is evaluated in simulation using a nonlinear model of a generic helicopter for on-line prediction of rotor blade pitch link loads arising from vehicle maneuvers.